Solvent-less solid state synthesis of dispersible metal and semiconducting metal sulfide nanocrystals (vol 6, pg 12006, 2018) - Bera, Abhijit; Busupalli, Balanagulu; Prasad, Bhagavatula L. V. (ACS Sustainable Chemistry & Engineering, 2020)

Selective electro-oxidation of phenol to 1,4-hydroquinone employing carbonaceous electrodes: surface modification is the key - Baravkar, Mayur D.; Prasad, Bhagavatula L. V. (New Journal of Chemistry, 2022)
The oxidation of phenol leading to 1,4-hydroquinone with high conversion, remarkable selectivity and an excellent yield (87% isolated) has been accomplished under electrolytic conditions in an aqueous medium employing carbon-based electrodes. To achieve this, various factors such as electrode stability, repeatability, and the type of product formed by the electrochemical oxidation of phenol have been investigated using cyclic voltammetry first and then organic transformations under optimized conditions were accomplished by constant current electrolysis. The voltammetric data clearly show that electrochemically generated intermediates passivate the surface of the typically used electrodes, leading to a decrease in their activity, which is a major problem concerning the transformation of phenol electro-oxidation to an industrially adaptable process. In this work, it is established that such difficulties could be circumvented using surface modified carbonaceous electrodes having disordered graphene-like structures and oxygen functional groups. It is also demonstrated that surface modified reticulated vitreous carbon (RVC) based electrodes could be used for electro-oxidation of phenol at a reasonably large scale. The electrolysis conditions have been optimized based on the mechanistic understanding leading to remarkable conversion of phenol with 87% selectivity to 1,4-hydroquinone.

Surface functionalization of inorganic nanoparticles with ligands: a necessary step for their utility - Bhattacharjee, Kaustav; Prasad, Bhagavatula L. V. (Chemical Society Reviews, 2023)
The importance of organic ligands in protecting inorganic nanoparticles and thus imparting the needed stabilization as colloidal dispersions was realised many years ago. Currently, the rational preparation of such nanoparticles with designed organic molecules/ligands resulting in the formation of functional nanoparticles (FNPs) that are tuned for a specific application is an area of immense research interest. The preparation of such FNPs for a desired application requires a clear understanding of the interactions at the nanoparticle (NP)-ligand and ligand-solvent interfaces, and demands a deep appreciation of the surface science and coordination chemistry. In this tutorial review, we briefly explore the evolution of surface-ligand chemistry and inform the readers that, apart from protecting the surface, ligands can modulate the physico-chemical properties of the underlying inorganic NPs as well. This review further presents the design principles for the rational preparation of such FNPs, where one or more ligand shells can be added to the nanoparticle surface, thereby improving the adaptability and amenability of the NP exterior towards the environment in which they are present, as required for a specific application.

Strategic design of a single-source precursor for in situ generation and integration of adherent species on Ni3S4 entangled-nanosheets for energy storage applications - Singh, Rahul; Thakur, Rohit; Sahu, Umasharan; Sahoo, Ramesh Chandra; Prasad, Bhagavatula L. V.; Matte, H. S. S. Ramakrishna (ACS Applied Nano Materials, 2025)
Synthesizing transition-metal chalcogenides (TMC) via a single-source precursor (SSP) route has shown great potential due to better reproducibility and control over stoichiometry, phase, and morphology. While the SSP converts into TMC, surfactants or coordinating species are essential to ensure dispersibility for further solution-based processing protocols. These additional species are typically highly toxic, difficult to remove, and adversely affect device performance. Here, as a proof of concept, design-induced in situ stabilized Ni3S4 (DiSNi) protocol demonstrates that strategic SSP design and optimized reaction conditions can facilitate directed chemical reactivity, gradually generating adhering species, which seamlessly integrate onto the metal chalcogenides, aiding the formation of stable dispersions without utilizing additional stabilizers. The proposed mechanism is validated by detailed strategic experiments and analysis, like X-ray photoelectron spectroscopy (XPS), accelerated dispersion stability measurements, and postsynthesis base treatment, which confirm the presence of in situ generated diethylammonium ion (DEA+) as the adherent and corroborate its role in dispersibility. The obtained Ni3S4 entangled-nanosheets are utilized to fabricate additive-free symmetric supercapacitors with organic electrolyte for charge storage over an extended potential window of 2.8 V and an energy density of 12.44 mu W h cm-2 at a power density of 0.42 mW cm-2. The devised DiSNi protocol showcases the importance of the SSP design for achieving multifunctionality. It is anticipated to have a broader impact on the role of careful design of SSP, making it an ideal contender for synthesizing transition-metal chalcogenides.
Keywords: dispersion stability; energy storages devices; low-boiling point solvents; nickel sulfide dispersions; organic electrolyte; single-source precursor; Supercapacitors

Synthesis framework for designing PtPdCoNiMn high-entropy alloy: a stable electrocatalyst for enhanced alkaline hydrogen evolution reaction - Chandran, M. Athira; Sahoo, Sudeshna; Singh, Ashutosh K.; Prasad, Bhagavatula L. V. (Small, 2025)
High entropy alloys (HEAs) are an emerging class of advanced materials characterized by their multifunctionality and potential to replace commercial catalysts in electrocatalytic water splitting. The synergy among the various alloyed elements in HEAs makes them particularly promising for applications in electrocatalysis. However, preparation of HEA via bottom-up approaches by avoiding the formation of mono, di, and tri metallic alloys in the nanoscale is challenging. This aspect is addressed, in this study by exploring the logical selection of solvents, reducing agents, and capping agents, along with their relative fractions, in the solvothermal synthesis of the HEA comprising platinum-palladium-cobalt-nickel-manganese (PtPdCoNiMn). It is established that the reducing capabilities of both the solvent and reducing agent are crucial for the reduction of each metal to form a single-phase HEA. The synthesized HEA (20 wt.%)/functionalized carbon (FC) demonstrates excellent performance as an HER catalyst, exhibiting a low overpotential of 48.7 mV at -10 mA cm-2 in an alkaline electrolyte. This performance is characterized by high reaction kinetics and stability at elevated current densities. Furthermore, the catalyst shows impressive performance in both simulated and actual seawater. This development reduces the reliance on platinum while enhancing the long-term durability and catalytic efficiency of the electrocatalyst.
Keywords: electrocatalysts; HER; high entropy alloys; solvothermal synthesis

Self-powered photodetection in AgBiS2 nanocrystals synthesized from AgBi-mixed-metal thiolate - Das, Mouli; Swathi, S. P.; Prasad, Bhagavatula L. V. (ACS Applied Nano Materials, 2026)
AgBiS2 has emerged as a promising optoelectronic material owing to its high absorption coefficient, environmentally friendly and abundant components, offering a sustainable alternative to lead- and cadmium-based chalcogenides. Realizing the full potential of AgBiS2 devices, however, requires scalable synthesis routes that include development of suitable precursors and minimize the use of harsh solvents, elevated temperatures, inert environments, etc. Here, we present a facile, solvent-free synthesis of phase pure AgBiS2 nanocrystals (NCs) at room temperature and under ambient conditions, enabled by the AgBi mixed-metal thiolate (AgBi-MMT) precursor complex. The initial choice of metal salts determines the nature of the metal thiolate intermediate complex, which subsequently influences the quality of the resulting AgBiS2 NCs. As a single-source precursor of the metals, AgBi-MMT enables controlled release of Ag+ and Bi3+ ions, yielding phase-pure AgBiS2 NCs. Furthermore, the MMT that is derived from AgI and BiI3 precursors promotes in situ surface passivation of the AgBiS2 NCs by iodide ions by trapping molecular I2 within its matrix. Under illumination, these iodide ions undergo reversible migration, generating a built-in potential and enabling self-powered photodetection in devices prepared from the as-synthesized NCs. This work expands the synthesis methodology of AgBiS2, highlighting the importance of metal thiolates as precursors in nanomaterial syntheses, and influence of iodine species in photo-operational devices.
Keywords: built-in potential; iodine; ion migration; layered; quantum dots